Production management model to reduce non-fulfillment of orders in Peruvian garment SMEs through 5S, SMED and standardization tools - Silva-Castro, Daniela (2022)
Currently, formal SMEs in the textile sector represent 16.4% of Peru's manufacturing SMEs, in other words, there are approximately 32,137 companies in this sector. The textile industry is the third largest contributor to manufacturing and is intensive in the generation of approximately 400,000 direct jobs. However, one of the main problems that prevents it from competing effectively with other countries in the region is related to non-fulfillment of orders. Also, lack of communication in the organization, inadequate operator training and employee resistance to new changes are the main barriers faced by companies in the sector during lean implementation. This research study will focus on reducing order non-compliance in an SME in the apparel sector using 5s techniques, SMED and standardization. An improvement is expected in relation to the problem, in addition, it is intended to develop a framework of lean practices that will serve companies in the sector. In this way, it contributes to the existing literature.